(untitled) (African Multidisciplinary Journal of Research, 2025)
Intense rivalry, technical developments, regulatory changes, and changes in the global financial landscape have all contributed to the growth of Kenya’s banking industry. Kenyan banks have been diversifying their revenue streams beyond interest income in an effort to improve their financial performance (FP). Despite these efforts, the industry’s financial performance steadily declined between 2013 and 2020, as seen by falling returns on assets (ROA), according to supervisory reports from the Central Bank of Kenya (CBK). The relationship between revenue diversification and FP is significantly influenced by the level of market competition. The aim of this study was to investigate the mediating role of competitive intensity on the relationship between income diversification and FP. This study was based on the Resource-Based View theory and employed a positivist philosophical framework. Using the census technique, the study examined secondary data from all Kenyan commercial banks that were in operation from 2013 to 2022. The study employed the Hirschman-Herfindahl Index to measure income diversification while the composite market share index represented competitive intensity. Panel ordinary least square regression models were employed in the study’s longitudinal descriptive research design to examine the relationships between the variables. Competitive intensity was found to partially mediate the relationship between income diversification and financial performance (β1 = .294, p = .00, β2 = .548, p = .00). The study concluded that the effect of income diversification on financial performance is not direct but is transmitted through competitive intensity. By promoting a healthy competitive environment that rewards innovation and efficiency, policymakers can indirectly enhance firms’ FP through diversified revenue streams. Future research could build on the existing findings by including other institutions in the financial sector and employing different metrics for the variables.